Breast Cancer Targeting of a Drug Delivery System through Postsynthetic Modification of Curcumin@N3-bio-MOF-100 via Click Chemistry - Alves, Renata C. [UNESP]; Schulte, Zachary M.; Luiz, Marcela T.; Bento Da Silva, Patrícia; Frem, Regina C. G. [UNESP]; Rosi, Nathaniel L.; Chorilli, Marlus [UNESP] (American Chemical Society (ACS), 2021)
Metal-organic frameworks (MOFs) offer many opportunities for applications across biology and medicine. Their wide range of chemical composition makes toxicologically acceptable formulation possible, and their high level of functionality enables possible applications as delivery systems for therapeutics agents. Surface modifications have been used in drug delivery systems to minimize their interaction with the bulk, improving their specificity as targeted carriers. Herein, we discuss a strategy to achieve a tumor-targeting drug-loaded MOF using clickchemistry to anchor functional folic acid (FA) molecules on the surface of N3-bio-MOF-100. Using curcumin (CCM) as an anticancer drug, we observed drug loading encapsulation efficiencies (DLEs) of 24.02 and 25.64% after soaking N3-bio-MOF-100 in CCM solutions for 1 day and 3 days, respectively. The success of postsynthetic modification of FA was confirmed by 1H NMR spectroscopy, Fourier transform infrared spectroscopy (FTIR), and liquid chromatography-mass spectrometry (LC-MS). The stimuli-responsive drug release studies demonstrated an increase of CCM released under acidic microenvironments. Moreover, the cell viability assay was performed on the 4T1 (breast cancer) cell line in the presence of CCM@N3-bio-MOF-100 and CCM@N3-bio-MOF-100/FA carriers to confirm its biological compatibility. In addition, a cellular uptake study was conducted to evaluate the targeting of tumor cells.